2010
DOI: 10.1097/jes.0b013e3181e372ef
|View full text |Cite
|
Sign up to set email alerts
|

Epimuscular Myofascial Force Transmission Implies Novel Principles for Muscular Mechanics

Abstract: In addition to the myotendinous junctions, muscle fibers also are connected to the extracellular matrix along their full peripheral length. Moreover, within the in vivo context, muscle is not an isolated entity. Instead, myofascial tissues connect muscles mechanically to neighboring muscular and nonmuscular structures, epimuscularly. This paper reviews the key aspects, determinants, and effects of epimuscular myofascial force transmission on muscular mechanics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
81
1
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 107 publications
(85 citation statements)
references
References 25 publications
0
81
1
3
Order By: Relevance
“…Fascia is continuous throughout the body, supporting various functions [8,[12][13]. Its continuity aids in force transmission both longitudinally and epimuscularly [14][15][16]. Through mechanotransduction, these forces may be transmitted at a cellular level, altering gene expression of fibroblasts and thereby changing the extracellular matrix composition [26][27][28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fascia is continuous throughout the body, supporting various functions [8,[12][13]. Its continuity aids in force transmission both longitudinally and epimuscularly [14][15][16]. Through mechanotransduction, these forces may be transmitted at a cellular level, altering gene expression of fibroblasts and thereby changing the extracellular matrix composition [26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…Forces exerted by any one muscle are known to transmit longitudinally along the myotendinous junction to exert an action across a joint. However, these forces may also be transmitted epimuscularly between muscle fibers and fascial connective tissues [14][15][16]. For example, it has been shown that after transecting the flexor carpi ulnaris (FCU) tendon, a residual wrist flexion force remains when the FCU muscle was contracted [17].…”
Section: Myofascial Force Transmissionmentioning
confidence: 99%
“…Влияние ботулинического токсина типа А на механику мышечного сокращения Местное введение БТА широко применяется для снижения повышенного мышечного тонуса вследствие блокирования рефлекса растяжения [37,38], что также может снижать и мышечную силу [39,40].…”
Section: Effect On Familial Releationshipsunclassified
“…Adductor longus [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] Так, по результатам метаанализа 70 исследований, оценивающих различные схемы введения БТА в мышцы верхней и нижней конечностей у 2163 взрослых паци-ентов со спастичностью, проведенного L. Nalysnyk и соавт. в 2013 г., было показано, что наиболее часто инъецируемыми мышцами являются икроножная (66,1 %), камбаловидная (54,7 %) и задняя большебер-цовая (50,5 %) [59].…”
Section: длинная приводящаяunclassified
See 1 more Smart Citation